Incidence and risk factors for pacemaker implantation in light chain and transthyretin cardiac amyloidosis. (3rd October 2022) - Porcari, A; Rossi, M; Cappelli, F; Canepa, M; Musumeci, B; Cipriani, A; Tini, G; Varra', G G; Argiro', A; Sessarego, E; Sinigiani, G; Di Bella, G; et al.
Abstract: Background: The incidence and risk factors of pacemaker (PM) implantation in patients with cardiac amyloidosis (CA) are largely unexplored. Purpose: We sought to characterise the trends in the incidence of permanent PM and to identify baseline predictors of future PM implantation in light chain (AL) and transthyretin (ATTR) CA. Methods: Multicentre, retrospective, observational study. Consecutive patients with AL and ATTR-CA diagnosed or referred at participating Centres between 2017 and 2020 were included. Clinical data recorded within ± 1 month from baseline evaluation were collected from electronic medical records. The primary outcome of the study was the need for clinically-indicated PM implantation. Reversible causes of conduction system disease were systematically ruled out before PM implantation. Patients with PM (n=41) and/or permanent defibrillator in situ (n=13) at the time of CA diagnosis were excluded. Results: The study population consisted of 405 patients: 29.4% AL, 14.6% variant ATTR and 56% wild-type ATTR; 82.5% were males, with median age 76 years. During a median follow-up of 33 months (interquartile range 21–46), 36 (8.9%) patients experienced the primary outcome: 10 patients with AL-CA, 2 with variant ATTR-CA and 24 with wild-type ATTR-CA (p=0.08). At multivariable analysis, history of atrial fibrillation (hazard ratio [HR] 3.80, p=0.002), PR interval (HR 1.013, p=0.002) and QRS >120 ms (HR 4.7, p=0.001) on baseline ECG were independently associated with PM implantation (Figure 1). In the individual patient, the contemporary presence of these 3 factors yielded the highest risk of PM implantation (HR 6.26, p=0.003). Conclusion: In a large cohort of AL and ATTR-CA, the incidence of PM implantation was high accounting for ≈9% of patients in the 3 years following the diagnosis. History of atrial fibrillation, longer PR interval and QRS >120 ms identified CA patients at high-risk of future PM implantation (Figure 2). CA patients with these features might need close monitoring during follow-up for the development of conduction system disease requiring PM implantation. Funding Acknowledgement: Type of funding sources: None.